1995
DOI: 10.1136/thx.50.6.658
|View full text |Cite
|
Sign up to set email alerts
|

Bronchus-associated lymphoid tissue (BALT) in the lungs of children who had died from sudden infant death syndrome and other causes.

Abstract: Background -Bronchus-associated lymphoid tissue (BALT) is well characterised in rabbits and rats. In humans, however, it does not seem to be present in the healthy adult lung, although it can develop after certain microbial stimulation. Methods -In the present study a consecutive series of lungs from 88 children who had died of sudden infant death syndrome (SIDS) and 34 control cases of comparable age were examined for the presence of BALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
2
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 14 publications
7
39
2
3
Order By: Relevance
“…It remains to be determined whether LALT is a distinct physiologic entity or a pathologic reaction in response to local infections or other environmental insults. Many children in whom LALT was identified postmortem had died because of sudden infant death syndrome (68,135). Little or no information is available regarding the role of LALT in antigen processing or presentation or the development of immunologic reactivity in the upper airway.…”
Section: Common Mucosal Immune Systemmentioning
confidence: 99%
“…It remains to be determined whether LALT is a distinct physiologic entity or a pathologic reaction in response to local infections or other environmental insults. Many children in whom LALT was identified postmortem had died because of sudden infant death syndrome (68,135). Little or no information is available regarding the role of LALT in antigen processing or presentation or the development of immunologic reactivity in the upper airway.…”
Section: Common Mucosal Immune Systemmentioning
confidence: 99%
“…Thus, BALT is obviously not found in healthy fetuses. In our own studies on lungs [22], BALT was found in 44% of 34 children who had died of trauma, malformation or other noninflammatory causes. There were mainly small aggregations but they showed all criteria of BALT with lymphoid infiltration of the overlying epithelium, HEV and partly active germinal centers ( fig.…”
Section: Balt In the Lung Of Children And Adolescentsmentioning
confidence: 99%
“…Other histological features are lymphocytic interstitial infiltration, follicular bronchiolitis and bronchus-associated lymphoid tissue hyperplasia [14]. In the current two patients the lymphocytic interstitial infiltration and the reactions of macrophages and pneumocytes that included giant cell formation were suggestive of a viral DNA integration.…”
Section: Discussionmentioning
confidence: 52%